Kandungan dan Serapan Mineral Pucuk Indigofera zollingeriana dari Tanaman dengan Kerapatan Tanam Berbeda: Mineral Content and Uptake of Indigofera zollingeriana on Different Planting Densities (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2021)
This experiment was conducted to evaluate the mineral contents of I. zollingeriana growing with different planting densities. The experiment was conducted in a randomized block design with three different planting densities (8,000 plants per ha, 13,333 plants per ha, and 20,000 plants per ha) and 3 replication. Plant biomass was analyzed for macro and micro mineral contents as well as Ca:P ratio. The results showed that increased planting densities significantly increased (p